Tseli i zadachi formirovaniya otraslevoi informatsionnoi sistemy - Lents, N. A. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
With the occurrence of the modern computer facilities our experts actively search for the ways of the problem of complex automation of the branch solving. Russia has interests in the information area and their support determined by the Doctrine of "The Information safety of the Russian Federation ". The necessity of the development of the modern information technologies, the Russian industry of the information including the industry of the resources of information, the telecommunications and connection, the support of the needs of the home market by its production and the output of this production on the global market, and the support of the accumulation, the safety and the effective utilization of Russian information resources is marked in the Doctrine. The task of today is the compilation of the information of the basic information flows in the uniform information resource, access to which will allow to increase the efficiency of the activity of Russian state sports committee, and also of all institutions and organizations of the branch. It is extremely important to involve the representatives of regions and sports organizations in this work. The opportunity of our branch to be integrated in the world information space and to take the maximum of benefits from the use of modern information technologies depends on the coordinated actions of all executors of the information system of the branch, their professionalism and enthusiasm in the solving of the tasks put before us.